The theme of a poet and poetry in the texts by Veronika Dolina - Mnich, Ludmiła (Przegląd Wschodnioeuropejski, 2025)
The article analyses the poetry by Veronika Dolina, a contemporary Russian singer-songwriter. The most significant factors that have shaped the new quality of Dolina’s songwriting are: the Russo-Ukrainian war, propaganda and censorship intensification, and the emigration of individuals with whom she has close familial and cultural ties. In this context, the themes that have already become traditional for Dolina’s work receive a new connotation. One of the central themes in her texts is the theme of a poet. This article focuses on the theme of a poet, which is realized in Dolina’s poetry in three variants: 1) a poet’s responsibility for what is happening in the country; 2) a poet as an atoning sacrifice; 3) a poet as a prophet. These variants are subsequently analyzed within the context of Dolina’s more recent literary works.